Desain Kendali Otomatis Prototype Inlet-Outlet Air Limbah KPPL - Rahmawati, Rahmawati; Amra, Siti; Kamal, Muhammad; Mardiyanto, Arief (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2025)
Wastewater treatment and retention ponds (KPPL) in industry play a crucial role in waste management. Controlling the inlet and outlet valves is essential to maintain flow balance and process efficiency. Currently, the KPPL at PT.X uses a manual method in valve control that relies on visual observation and sampling, which is limited in accuracy and responsiveness. Therefore, it is necessary to design an automatic valve control prototype to improve the performance of the wastewater treatment system at PT. X. This study aims to build an automatic control system that uses level and pH sensors and a DC motor to regulate wastewater flow. This system uses hysteresis on-off control to prevent excessive energy consumption and extend component life by reducing the frequency of valve opening and closing. The ultrasonic sensor detects the water level, while the pH sensor monitors the water quality before being discharged into the sea. Testing shows the accuracy of the sensors, with an average error of 0.94% for the level sensor and 0.9% for the pH sensor. Hysteresis control keeps the pump and motor off when the water level is within the safe range, which increases efficiency and reduces wear. This system provides more precise control over wastewater flow, ensures safe and environmentally friendly disposal, and reduces manual intervention and the risk of operational errors.Keywords— hysteresis, on-off control, KPPL, pH, ultrasonic sensor